Strain and Displacement Measurements in Reinforced Self-Compacting Concrete Beams with Openings Using Digital Image Correlation Technique - Alexandra Coșa; Bogdan Hegheș; Camelia Negruțiu; Zoltan Kiss (Proceedings, 2020)
In structural engineering, strain and displacement are critical parameters, and measuring these parameters outside of the laboratory is a challenge for concrete researchers. Recent advances have enabled digital image correlation (DIC) to calculate the concrete surface displacements of chosen targets in a series of images recorded during an experiment. This paper presents a comparison between traditional and optical measurements to evaluate the efficiency of the DIC technique in recording the deformations of reinforced concrete beams. Tests were perfomed on two small-scale reinforced self-compacting concrete beams with small circular openings in 3-point bending.